Postoperative evaluation of recurrence in operated chronic otitis media cases with cholesteatoma - Ejder Ciğer; Mehmet Doğan Özkul; İbrahim Çukurova; Suat Kaptaner; Ömer Uğur; Alper Tatar; Metin İber (Turkish Archives of Otorhinolaryngology, 2004)

(untitled)
50 cases suffering from chronic otitis media with cholesteatoma operated at SSK Educational Hospital, ENTHead and Neck Surgery Clinic were included. Every patient was examined by otoscopy and high resolution CT-scanning of the temporal bone before a second-look operation. Preoperative examinations were compared with the intraoperative findings. 42 (84%) patients were operated with open technique and the other 8 (16%) closed technique tympanoplasty. Recurrent cholesteatoma was seen at 13 (30.9%) of the patients treated by open technique and at 1 (12.5%) patient treated by closed technique, which ends 14 (28%) totally. Cholesteatoma was seen in sinus tympani at 5 (35.7%), in epitympanum at 6 (42.8%) and in the middle ear and the mastoid cavity 3 (21.4 %) of these cases. Statistical correlation was found 89% between the otomicroscopic findings of preoperative and intraoperative findings. Also it was found 69% between the preoperative CT-scan and intraoperative findings. At 71.5 % of the patients, recurrent disease was seen within 3 years. No statistical correlation was found among the age, sex and followup criteria of the patients (p>0.05). The importance of otoscopic examination, CT-scanning of the temporal bone and follow- up period was discussed in the light of the results of these investigations.